\(2\dfrac{3}{4}:x=3\dfrac{1}{7}:0,01\)
\(\dfrac{11}{4}:x=\dfrac{22}{7}:\dfrac{1}{100}\)
\(\dfrac{11}{4}:x=\dfrac{2200}{7}\)
\(x=\dfrac{11}{4}:\dfrac{2200}{7}\)
\(x=\dfrac{7}{800}\)
\(2\dfrac{3}{4}:x=3\dfrac{1}{7}:0,01\)
\(\dfrac{11}{4}:x=\dfrac{22}{7}:\dfrac{1}{100}\)
\(\dfrac{11}{4}:x=\dfrac{2200}{7}\)
\(x=\dfrac{11}{4}:\dfrac{2200}{7}\)
\(x=\dfrac{7}{800}\)
Tìm x biết :
1) \(\dfrac{-7}{x+1}=\dfrac{-x-1}{\dfrac{4}{7}}\)
2) \(\dfrac{x-3}{x+5}=\dfrac{5}{7}\)
3) \(\dfrac{x+1}{2x+1}=\dfrac{0,5x+2}{x+3}\)
4) \(\dfrac{3x+2}{5x+7}=\dfrac{3x-1}{5x+1}\)
1,\(\dfrac{3}{16}\)- ( x - \(\dfrac{5}{4}\) ) - ( \(\dfrac{3}{4}\) + \(\dfrac{-7}{8}\) - 1 ) = \(2\dfrac{1}{2}\)
2,\(\dfrac{1}{2}\) . ( \(\dfrac{1}{6}\) - \(\dfrac{9}{10}\) ) = \(\dfrac{1}{5}\) - x + ( \(\dfrac{1}{15}\) - \(\dfrac{-1}{5}\) )
Giúp mik nhanh với ạ
\(\dfrac{4}{9}.19\dfrac{1}{3}+\dfrac{-4}{9}.39\dfrac{1}{3}+\dfrac{-3^2}{5}:\left(-0,2\right)\)
\(\dfrac{\left(-5^3\right)^2}{27}.\dfrac{3}{23}.\dfrac{6^2}{-5^6}\)
\(1\dfrac{4}{23}+\dfrac{5}{21}-\dfrac{4}{23}+0,5+\dfrac{16}{21}\)
\(\dfrac{3}{7}.19\dfrac{1}{3}-\dfrac{3}{7}:33\dfrac{1}{3}\)
\(\dfrac{3}{4}-\left(x+\dfrac{1}{2}\right)=\dfrac{4}{5}\)
x:(-2,14)=(-3,12):1,2
a)\(\dfrac{\left(x+\dfrac{3}{4}\right)\cdot\dfrac{7}{2}-\dfrac{1}{6}}{-\left(\dfrac{4}{5}+\dfrac{1}{3}\right)\cdot\dfrac{1}{2}+1}=2\dfrac{33}{52}\)
b)\(\dfrac{\left(5-\dfrac{2}{7}\right)\cdot\dfrac{7}{9}:\dfrac{3}{5}}{\left(3x-\dfrac{5}{6}\right):\dfrac{1}{7}}=5\dfrac{5}{21}\)
Bài 7: Tìm X
a) \(\dfrac{\left(x+\dfrac{3}{4}\right)\cdot\dfrac{7}{2}-\dfrac{1}{6}}{-\left(\dfrac{4}{5}+\dfrac{1}{3}\right)\cdot\dfrac{1}{2}+1}=2\dfrac{33}{52}\)
b)\(\dfrac{\left(5-\dfrac{2}{7}\right)\cdot\dfrac{7}{9}\cdot\dfrac{3}{5}}{\left(3x-\dfrac{5}{6}\right):\dfrac{1}{7}}=5\dfrac{5}{21}\)
Tìm x:
3\(\dfrac{1}{14}\) - 5\(\dfrac{1}{3}\) - \(\dfrac{4}{7}\) + \(\dfrac{11}{21}\) = x -\(\dfrac{1}{2}\)
Làm ra bài giải giúp mk vs
Tìm x , biết
a) \(\left|x-4\right|=6\)
b) \(\dfrac{x}{5}=\dfrac{9}{7}\)
c) \(1\dfrac{2}{5}x+\dfrac{3}{7}=\dfrac{-4}{5}\)
d) \(\left|x+\dfrac{2}{3}\right|+2=2\dfrac{1}{3}\)
Tính nhanh
\(\dfrac{\dfrac{1}{3}-\dfrac{1}{7}-\dfrac{1}{13}}{\dfrac{2}{3}-\dfrac{2}{7}-\dfrac{2}{13}}.\dfrac{\dfrac{3}{4}-\dfrac{3}{16}-\dfrac{3}{64}-\dfrac{3}{264}}{1-\dfrac{1}{4}-\dfrac{1}{16}-\dfrac{1}{64}}+\dfrac{5}{8}\)
\(\dfrac{2^{18}}{32^3}.\dfrac{27^4}{54^3}\) \(\dfrac{x+1}{9}=\dfrac{4}{x+1}\) Tìm x, y biết:
\(\dfrac{40^4}{120^4}:\dfrac{130^3}{390^3}\) \(19.5^{2x+7}=475\) 5x=4y và y-x=7
\(2^x.8\) \(\dfrac{2x}{5}=\dfrac{10}{x}\)
\((\dfrac{1}{2})^x=\dfrac{1}{32}\) \(33^x:11^x=243\)